Resilient organizational capabilities in NTBFs. Concept and variables as dynamic and adaptive capabilities - Eduardo Bueno Campos; Cecilia Murcia Rivera; Carlos Merino Moreno (Small Business International Review)
In this paper we propose the concepts and variables that characterize resilient organizational capabilities (onwards ROC that can be viewed as dynamic capabilities. The concept of resilience highlights the ability to overcome trauma and the power to emerge more reinforced, considering the concept of “lessons learned” as the basis for its development. There are two key factors: attitudes and culture that can be transformed into a concept of resilience. In this work, the concept and characteristics of the ROC or “adaptive capabilities” generating innovation in the field of SMEs are presented. Also, the role of dynamic capabilities and intellectual capital that has been playing to date will be explained. In this research a methodological triangulation and a qualitative analysis to data on a Case Studies in new technology based firms (NTBFs) of the Scientific Park of Madrid and Colombian SMEs are realized. And will be completed with a quantitative analysis through the survey of these same two groups. The results of the comparative study show differences in analysed ROC, explained by cultural or economic themes, or by the sectors or sizes to which the companies of the reference groups belong, which is the basis for a future line of research.